Association of Neck and Back Angle with Muscle Endurance Among Asymptomatic Smartphone Users: A Correlation Study (International Journal of Physiotherapy, 2025)
Background: Smartphones are becoming prevalent in daily life, but continuous use, especially among young adults, is frequently linked to poor posture, such as neck flexion, which can lead to musculoskeletal problems and muscular weakness. This correlational study investigated the relationship between neck and back angles and muscle endurance in asymptomatic smartphone users.Methods: It is an observational study, with a total of 94 asymptomatic smartphone users aged 19-24 years, including 30 males and 64 females, who were assessed for neck and back endurance using a standardized neck and back endurance test, and their neck and back angles during smartphone use were measured from photographs using Kinovea software.Results: The study found a significant negative correlation between increased neck and back flexion angles and reduced muscle endurance (p < 0.05). Posture during smartphone use was identified as the primary factor influencing endurance, whereas smartphone use duration showed no significant correlation with neck or back endurance (p > 0.05).Conclusion: Maintaining good posture while using smartphones is important to mitigate the risk of reduced muscle endurance and potential musculoskeletal problems.